Rare Bloodstream Infection of Rhodococcus rhodochrous as the Prodromal Signal for Malignancy - Liu J; Wu X (Infection and Drug Resistance)
Jia Liu,1 Xintong Wu2 1Department of Pulmonary and Critical Care Medicine, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 2Department of Neurology, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of ChinaCorrespondence: Xintong Wu, Department of Neurology, West China Hospital, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu City, Sichuan Province, 610041, People’s Republic of China, Email 36853839@qq.comAbstract: Rhodococcus-associated infections are extremely rare, and previous publications have indicated that such infections are primarily observed among individuals with HIV. Limited information is available regarding therapy, and no clear consensus has been reached to guide treatment. Here, we report the first case of bloodstream infection with Rhodococcus rhodochrous in a non-HIV patient with a viral intracranial infection. During follow-up, lymph node biopsy and bone marrow aspiration were performed because superficial lymphadenectasis had failed to regress as expected within 3 months. The patient was newly diagnosed with nodal T-follicular helper cell lymphoma, angioimmunoblastic-type. For cases of rare infection or co-infection, screening for pathogenic microorganisms is the priority, and several methods should be employed, such as microorganism culture, antigen and antibody detection, and metagenomic next-generation sequencing. In retrospect to integrated case management, our case indicated that early malignancy screening is significant for early diagnosis and treatment of occult cancer during patients with rare opportunistic infections.Keywords: Rhodococcus rhodochrous, bloodstream infection, intracranial infection, nodal T-follicular helper cell lymphoma